Pengaruh Media Video Terhadap Kemampuan Menulis Puisi Kelas V Sekolah Dasar Se- Kota Bengkulu - Bela Mardalea; Nani Yuliantini; Dwi Anggraini (JURIDIKDAS, 2019)
This research is to know the influence of the use of video media on the ability to write poetry of class V students in SD Negeri as Bengkulu City. The type of this research is quantitative research and the research design is the matching only posttest control design, taking the test one time that is done after giving treatment (treatment) in the sample class. The population in this study is the students of grade V in Bengkulu City. The sample in this research is VA class SD Negeri 38 Kota Bengkulu as experiment class and VB SD Negeri 58 Kota Bengkulu as control class with stratified random sampling sampling technique. The research instrument uses a description test (essay). Data of research result is analyzed by using inferential analysis that is t-test. Based on the results of data analysis obtained tcount of 3, 43 and ttable value of 2.019 with a significant level of 5% means Ha accepted. It can be concluded that there is influence of the use of video media on the ability of writing poetry of class V students in SD Negeri as Bengkulu City.